Analisis Profitabilitas Terhadap Manajemen Risiko Pada Perusahaan Perbankan Yang Terdaftar Di BEI - Ade Wiyatama; Dhani Ichsanuddin Nur (COMPETITIVE, 2022)
The purpose of this study is to determine and analyze the effect of market risk, liquidity risk, capital adequacy risk, operational risk as a factor considered by companies on the profitability of banking companies listed on the Indonesia Stock Exchange for the period 2016 - 2019. This study used purposive sampling and used linear regression analysis using the SPSS program as a testing tool. The results of this study indicate that the independent variable, namely Market Risk, can contribute to determining profitability. Liquidity Risk can contribute in determining Profitability. Operational Risk can contribute in determining Profitability. Meanwhile, Capital Adequacy Risk cannot contribute to determining Profitability.